Mapping Of Vegetation And Mangrove Distribution Level In Batam Island Using SPOT-5 Satellite Imagery - Rizki, Fajar; Situmorang, Arini Dewi Lestari; Wau, Nirwana; Lubis, Muhammad Zainuddin; Anurogo, Wenang (UIR PRESS, 2017)
Mangrove is a plant that plays a significant role in the balance of the ecosystem and coastal environment. Batam Island which is one of the island in Batam island become one of the areas rich in mangrove plants. As time goes by, mangrove forests are getting worse. This research uses SPOT-5 imagery data in analyzing mangrove density value in Batam island with MSAVI (Modified Soil Adjusted Vegetation Index) method. The results of this study have mangrove density in Batam Island which is divided into four classes, which is very tenuous, tenuous, medium, and very tightly where Batam Island is dominated by a class of density. Theoretically, NDVI values range from -1 to +1 but the mangrove vegetation index values are generally in the range between +0,1 to +0,7. NDVI values greater than this range are associated with a representation of a better level of vegetation health in the islands of Batam.